An analysis types of figurative languages found in richard marx's song lyrics - Wibawa, I Gede Adi Guna; Putri , IGA Vina Widiadnya; Juniartha , I Wayan (Institut Pariwisata dan Bisnis Internasional, 2020)
This research aims to identify the kinds of figurative languages used in the chosen song lyrics of Richard Marx and to examine the meanings of figurative languages in the song lyrics of Richard Marx. Several song lyrics from Richard Marx that were randomly taken are the data base of this analysis. In the analysis of data from this report, descriptive and qualitative methods were used. The theory of Knickerbocker and Reninger (1963: 367) studied the types of figurative languages and also the accepted theory of meaning proposed by Leech (1981: 16) will be analyzed in the selected song lyrics of Richard Marx to explain the meaning of figurative language. The researcher assumes, after the study has been finished, that the chosen song lyrics of Richard Marx consist of 20 lyrics that used figurative language. Therefore, it was found 7 types of figurative language, there are simile (16, 67%), metaphor (5, 56%), personification (19, 44%), irony (2, 78%), hyperbole (47, 22%), synecdoche (2, 78%) and metonymy (2, 78).